Psychotic Symptoms Associated with the use of Dopaminergic Drugs, in Patients with Cocaine Dependence or Abuse - Roncero, Carlos; C. Abad, Alfonso; Padilla-Mata, Antonio; Ros-Cucurull, Elena; Barral, Carmen; Casas, Miquel; Grau-Lopez, Lara (Current Neuropharmacology, 2017)
Background: In the field of dual diagnosis, physicians are frequently presented with pharmacological questions. Questions about the risk of developing psychotic symptoms in cocaine users who need treatment with dopaminergic drugs could lead to an undertreatment. Objective: Review the presence of psychotic symptoms in patients with cocaine abuse/dependence, in treatment with dopaminergic drugs. Methods: Systematic PubMed searches were conducted including December 2014, using the keywords: “cocaine”, dopaminergic drug (“disulfuram-methylphenidate-bupropion-bromocriptine-sibutramineapomorphine- caffeine”) and (“psychosis-psychotic symptoms-delusional-paranoia”). Articles in English, Spanish, Portuguese, French, and Italian were included. Articles in which there was no history of cocaine abuse/dependence, absence of psychotic symptoms, systematic reviews, and animal studies, were excluded. Results: 313 papers were reviewed. 7 articles fulfilled the inclusion-exclusion criteria. There is a clinical trial including 8 cocaine-dependent patients using disulfiram in which 3 of them presented psychotic symptoms and 6 case-reports: disulfuram (1), methylphenidate (1), disulfiram with methylphenidate (2), and bupropion (2), reporting psychotic symptoms, especially delusions of reference and persecutory ideation. Conclusion: Few cases have been described, which suggests that the appearance of these symptoms is infrequent. The synergy of dopaminergic effects or the dopaminergic sensitization in chronic consumption are the explanatory theories proposed by the authors. In these cases, a relationship was found between taking these drugs and the appearance of psychotic symptoms. Given the low number of studies found, further research is required. The risk of psychotic symptoms seems to be acceptable if we compare it with the benefits for the patients but a closer monitoring seems to be advisable.
Keywords: psychotic symptoms